Mono- and Dicationic DABCO/Quinuclidine Composed Nanomaterials for the Loading of Steroidal Drug: 32 Factorial Design and Physicochemical Characterization - Fernandes, Ana R. (2021)
Oil-in-water nanoemulsions (NEs) are considered a suitable nanotechnological approach to improve the eye-related bioavailability of lipophilic drugs. The potential of cationic NEs is prominent due to the electrostatic interaction that occurs between the positively charged droplets with the negatively charged mucins present in the tear film. This interaction offers prolonged NEs residence at the ocular surface, increasing the drug absorption. Triamcinolone acetonide (TA) is one of the first pharmacologic strategies applied as an intravitreal injection in the treatment of age-related macular degeneration (AMD). Newly synthesized quaternary derivatives of 1,4-diazabicyclo[2.2.2]octane (DABCO) and quinuclidine surfactants have been screened with the purpose to select the best compound to formulate long-term stable NEs that combine the best physicochemical properties for the loading of TA intended for ocular administration.